Survival Rates of Breast Cancer Patients Aged 40 to 49 Years according to Detection Modality in Korea: Screening Ultrasound versus Mammography - Won, So Yeon; Park, Hyung Seok; Kim, Eun-Kyung; Kim, Seung Il; Moon, Hee Jung; Yoon, Jung Hyun; Park, Vivian Youngjean; Park, Seho; Kim, Min Jung; Cho, Young Up; Park, Byeong-Woo (Korean journal of radiology, 2021)
The aim of this study was to compare the survival rates of Korean females aged 40 to 49 years with breast cancer detected by supplemental screening ultrasound (US) or screening mammography alone. This single-institution retrospective study included 240 patients with breast cancer (mean age, 45.1 ± 2.8 years) detected by US or mammography who had undergone breast surgery between 2003 and 2008. Medical records were reviewed for clinicopathologic characteristics and detection methods. Disease-free survival (DFS) and overall survival (OS) were compared between patients with breast cancer in the US and mammography groups using the log-rank test. Multivariable cox regression analysis was used to identify independent variables associated with DFS and OS. Among the 240 cases of breast cancer, 43 were detected by supplemental screening US and 197 by screening mammography (mean follow-up: 7.4 years, 93.3% with dense breasts). There were 19 recurrences and 16 deaths, all occurring in the mammography group. While the US group did not differ from the mammography group in tumor stage, the patients in this group were more likely to undergo breast-conserving surgery and radiation therapy than the mammography group. The US group also showed better DFS ( = 0.016); however, OS did not differ between the two groups ( = 0.058). In the multivariable analysis, the US group showed a lower risk of recurrence (hazard ratio, 0.097; 95% confidence interval, 0.001-0.705) compared to the mammography group. Our study found that Korean females aged 40-49 years with US-detected breast cancer showed better DFS than those with mammography-detected breast cancer. However, there were no statistically significant differences in OS.